La position respective du nouveau droit international privé et des engagements internationaux de la Pologne (Contemporary Central & East European Law, 1967)
The article tackles the problem of the relationship between the rules introduced by the codification of Polish private international law introduced on the 12th November 1965  and the rules of international law. Such an analysis is crucial because previous legal act regulating private international law from the 2nd August 1926 had not got any provisions concerning this matter.The proposition of the text provided the superiority of the international law over national legislation, saying that the dispositions of private international law do not derogate provisions of any international convention in force, but the final version constitutes that the provisions of polish private international law should not be applied if they are contrary to any international convention to which Poland is a party. This change seems justified since it is the court who decides which law should be applied if the conflict of norms occurred.In the further part of the article, the necessity of aforementioned provision is analysed. The lack of such provision in the law from 1926 did not prevent the court from applying the international conventions’ norms.The latter part of the article is devoted to the bilateral conventions, which are concluded to be slightly more important as signed with the greater number of countries and more detailed. Moreover, most of them are signed with other socialist countries.The further part of the article is dedicated to the analysis of the binding international conventions, both multilateral and bilateral, that may contain regulations contrary to the provisions of Polish private international law. Firstly, the Polish regulation concerning marriage and rights of spouses is analysed in points which are contrary to the convention signed in la Haye in 1905. Secondly, legal provisions concerning divorce and guardianship of minors are analysed in points where they are in conflict with the provisions of convention signed in la Haye on the 12th June 1902 and the question of curatorship which was regulated by the convention signed in la Haye on 17th July 1905.It is worth mentioning that, even if national legal provision is contrary to the norm of international convention, the court may apply national regulation if application of the international norm infringes the norms of greater value – for example the equality of sexes or prohibition of discrimination. There is also a short revision of bilateral conventions biding the Polish People’s Republic followed by the conclusion that their provisions are mainly similar to the provisions of codification from 1965. The analysis of all the exceptions is beyond the scope of the article, but some of them are treated in the further part of it (legal capacity of natural or legal persons, capacity to contract marriage, form of marriage, divorce, law on succession). The bilateral conventions taken into account are those signed with other socialist countries. The only convention taken into account which does not concern the Eastern Bloc country is the one signed with Austria.